Implementation of Y Model Work Strategy as A Policing Model for Transnasional Organized Crime in Bali - Reinhard Golose, Petrus (Technium Social Sciences Journal, 2020)
Bali is one of the very vulnerable areas of being an operational area for transnational organized crime. Its strategic and popular position as an international tourist destination has become a strategic route as a transit point and a destination for operations for perpetrators of transnational organized crime. In dealing with this problem, the Bali regional police have implemented the Y model work strategy to deal with transnational organized crime. The Bali provincial police carried out several essential policies in the context of the Y model work strategy, namely the formation of a counter transnational-organized crime task force and increasing cooperation both nationally and internationally. Collaboration is carried out to facilitate the exchange of information related to perpetrators of transnational organized crime.